Managing the Marginal: Regulating and Negotiating Decency in Vancouver's Beer Parlours, 1925-1954 - Campbell, Robert A. (Labour / Le Travail, 1999)
Little historical work has been done in Canada on public drinking in general and public drinking after prohibition in particular. For British Columbia this neglect is a real oversight because hotel saloons were transformed into hotel beer parlours after prohibition. The first parlours opened in Vancouver in 1925, and, like saloons, they catered to a working-class clientele. Parlours held sway until 1954 when a new Government Liquor Act provided for additional venues of public drinking. One did not have to sit long in a Vancouver parlour to realize that more than alcohol consumption was being regulated. Parlours also regulated class, gender and sexuality, and race.